2021
DOI: 10.3390/ijerph18094482
|View full text |Cite
|
Sign up to set email alerts
|

Moving through Motherhood: Involving the Public in Research to Inform Physical Activity Promotion throughout Pregnancy and Beyond

Abstract: Information received by women regarding physical activity during and after pregnancy often lacks clarity and may be conflicting and confusing. Without clear, engaging, accessible guidance centred on the experiences of pregnancy and parenting, the benefits of physical activity can be lost. We describe a collaborative process to inform the design of evidence-based, user-centred physical activity resources which reflect diverse experiences of pregnancy and early parenthood. Two iterative, collaborative phases inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…It is evident that supporting women to remain active during pregnancy needs to go beyond providing women with standardized medical information relating to exercise. Instead, guidance should consider the individual constraints and needs of pregnant women (eg, lifestyle) 7,16,27. Therefore, it is important that women are provided with tailored exercise guidance during pregnancy, which aligns with their preferred exercise habits, in a similar manner to that which was found during postpartum with women receiving broadly sourced running advice.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that supporting women to remain active during pregnancy needs to go beyond providing women with standardized medical information relating to exercise. Instead, guidance should consider the individual constraints and needs of pregnant women (eg, lifestyle) 7,16,27. Therefore, it is important that women are provided with tailored exercise guidance during pregnancy, which aligns with their preferred exercise habits, in a similar manner to that which was found during postpartum with women receiving broadly sourced running advice.…”
Section: Discussionmentioning
confidence: 99%
“…This is a more positive framing than the concept of the "third shift" described by Dworkin and Wachs (p610), [75] where physical activity becomes another task for women to complete after their paid work and unpaid work in the home. The benefits of positive framing or "gain framing", particularly the social and mental health benefits that will accrue from participation in physical activity have been highlighted by others working with low SES groups [49,50,52]. Some mothers will require more encouragement and support than is currently available to them to become physically active because they are starting from a position that denies the need to undertake exercise, either because they feel physically unable to exercise or because they feel their everyday activities provide sufficient exercise.…”
Section: Discussionmentioning
confidence: 99%
“…To change, mothers will need information presented in a way that they can readily adopt it in their busy lives, acknowledging both social constraints and inherent anxieties. Salmon et al [52] found that mothers responded positively to "like me" stories with which they could identify. The mothers that participated in this study are part of a general trend in the developed world away from an active lifestyle towards increased sedentary behavior [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations